Merger InJourney Airports: Optimalisasi Sinergi Operasional dan Keuangan dalam Industri Aviasi Indonesia - Ivan Kurniawan, Abraham; Mathew Hadap, Billy; Morgan Gemiartha, Celine; Edbert Sudarsono, Jethson; Adeline Yusuf, Keona; Linawati, Nanik (DINASTI RESEARCH, 2025)
Penelitian berjudul